Strategi Pengembangan Website sebagai Media Informasi Desa di Kabupaten Klungkung - I M. Oka Widyantara; L Linawati; I P. A. Mertasana; W. Setiawan (Buletin Udayana Mengabdi, 2016)
Our research was develop web applications as media information for villages in Klungkung Regency, implementation strategy involves participation of village’s councilor, IT volunteer, Udayana University community services team, and Klungkung Government. The research focused on the realization of village website based on Content Management System (CMS), and strategy training for website administrators. Main target, the website was built to inform the potential competitive, like menus: village profile, village potential, administration, statistics, regulations, budget transparency, services and village news. In the implementation phase, the study used a model of collaborative strategies, namely the construction of CMS and training conducted by Unud community services team, domain and hosting was prepared by Klungkung regency, and assistance administrator by IT volunteers. The website content training aimed at the entire councilor and IT volunteers. Research showed that used CMS website for entire village can accelerate and simplify for continue development other village website in Klungkung Regency. Development model village website with collaborative strategy generate patterns based on implementation assistance, where a website administrator would be helped by IT volunteers to fill website content. This strategy would be able to help build website for entire village in Klungkung and would be managed independently by village administrator.